The legal regime of the Arctic - new challenges and dimensions (Journal of actual problems of jurisprudence, 2019)
The international legal regime of the Arctic with regard to the speci fi cs of ice cover is based primarily on the UN Convention onthe Law of the Sea since 1982. There is currently no military con fl ict for the possession of the territory, the demarcation of borders or thesea-bed. However, this does not exclude the possibility of a potential con fl ict in the near or distant perspective. The purpose of this paperis an analysis of the legal regime of Arctic, continental shelf, particular disputes on the establishment of boundaries between coastalwaters, sovereign economic zones, continental shelves and the right to territorial sovereignty over the land in the Arctic.